Pendampingan Penerapan CHSE pada Pengelolaan Homestay Dusun Ciceuri Tengah di Desa Sukamandi Masagi - Ramadhani, Alya; Brillian Prince; Fedrina, Rezka (Satwika: Jurnal Pengabdian Kepada Masyarakat, 2024)
Assistance in implementing CHSE for homestay managers in Sukamandi Masagi Village is certainly very important for the community. Sukamandi Masagi Village is a tourist village that is attractive to tourists for educational activities. This was seen when the village was used by Labschool Cirendeu students for live-in activities in 2022 and 2023 respectively. The need for insight and knowledge related to homestay management in accordance with CHSE standards so that homestay managers can know the standard criteria for a decent homestay. CHSE is a very important requirement in homestays because its application can increase security and safety for tourists. In this case, the goal is to increase knowledge and aspects of good and correct homestay management.